Designing a Low Cost Electrospinning Device for Practical Learning in a Bioengineering Biomaterials Course - Villareal Gómez, L J (Revista Mexicana de Ingenieria Biomedica, 2016)
The electrospinning device is used in the biomaterials research field nowadays for fabricating nanofibers that can be used for manufacturing artificial skin and muscular tissue, blood vessels (vascular grafts), orthopedic components (bones, cartilages, and ligaments/tendon), and peripheral or central nervous system components. Electrospun nanofibers act as ideal scaffolds for tissue engineering and drug delivery systems because they can mimic the functions of native extracellular matrices. A low cost electrospinning device was designed and built for undergraduate practical learning in the Biomaterials course in the area of Bioengineering at Universidad Autónoma de Baja California, México. The methodology includes 3D CAD designing, manufacturing of the acrylic cabinet, different collectors and the fabrication of poly (vinyl alcohol) nanofibrous scaffolds, in order to validate the functionality of the electrospinning system. The prototype is an affordable device; its cost is 95% less than the laboratory commercial devices.